Prognostic Value of Myeloid Marker Positivity and its Association with Prognostic Factors in Pediatric Acute Lymphoblastic Leukemia - Neval Topal; Seda Yılmaz Semerci; Muharrem Çiçek; Gönül Aydoğan (Trends in Pediatrics, 2021)
Objective: The aim of this study is to investigate the effect of myeloid marker positivity on prognosis and its relationship with classical prognostic factors in acute lymphoblastic leukemia (ALL).